2017
DOI: 10.1111/trf.14447
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of umbilical cord blood collection quality

Abstract: After 30 years of hematopoietic stem cell use for various indications, umbilical cord blood is considered as an established source of cells with marrow and postmobilization peripheral blood. The limited number of cells still remains a problematic element restricting their use, especially in adults who require to be grafted with a higher cell number. Improving the quality of harvested cord blood, at least in terms of volume and amount of cells, is essential to decrease the number of discarded units. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 78 publications
(606 reference statements)
2
17
0
2
Order By: Relevance
“…To date, some studies have observed that delayed umbilical cord clamping and the in utero collection mode have some negative correlations with the volume of UCB collection [4,5]. The current results may be the same for the latter.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…To date, some studies have observed that delayed umbilical cord clamping and the in utero collection mode have some negative correlations with the volume of UCB collection [4,5]. The current results may be the same for the latter.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, some obstetric factors such as greater infant and placental weights have also been proposed as effective factors facilitating UCB collection with sufficient cellular richness [4,5,13]. However, the weights of Japanese infants and placentae may be lower than those in the countries reported previously [4,5,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faivre et al examined several variables related to the parturient, pregnancy, labor, delivery, collection, the newborn, the umbilical cord, and the placenta in their comprehensive review that included 71 related articles (26). Maternal age at delivery was assessed in 28 of 71 articles, and it was found not to be associated with favorable CBU collection parameters in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Faivre et al indicated that iron-related maternal blood variables did not seem to affect the CBU quality according to the literature they reviewed (26). They also evaluated the effect of gestational age at birth by reviewing 24 articles.…”
Section: Discussionmentioning
confidence: 99%